2005
DOI: 10.1002/jms.847
|View full text |Cite
|
Sign up to set email alerts
|

Novel lipid hydroperoxide‐derived hemoglobin histidine adducts as biomarkers of oxidative stress

Abstract: Hemoglobin (Hb) adducts have long been used as dosimeters of exposure to xenobiotics and endogenously formed reactive metabolites. In this study, hemoglobin chains were separated from each other and their prosthetic heme groups and reacted with 4-oxo-2-nonenal, a major breakdown product of lipid hydroperoxides. The adducts were characterized by matrix-assisted laser desorption/ionization-mass spectrometry (MALDI-TOF/MS) analysis of the intact proteins and by a combination of liquid chromatography/electrospray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 49 publications
(84 reference statements)
2
30
0
Order By: Relevance
“…These adducts are relatively unstable and could be further converted into stable products including dihydrofuran, dihydropyrrole, and isomeric 4-ketoamide derivatives originating from the reaction of ONE with lysine (41) and a substituted imidazole derivative with arginine (42). ONE also forms furan derivatives upon its reaction with the cysteine and histidine derivatives (43,44). In our recent study, we carried out a comprehensive study on the identification of the ONE-N-acetyl-L-cysteine adducts and identified several advanced reaction products that originated from the initial Michael adducts (45).…”
Section: Discussionmentioning
confidence: 99%
“…These adducts are relatively unstable and could be further converted into stable products including dihydrofuran, dihydropyrrole, and isomeric 4-ketoamide derivatives originating from the reaction of ONE with lysine (41) and a substituted imidazole derivative with arginine (42). ONE also forms furan derivatives upon its reaction with the cysteine and histidine derivatives (43,44). In our recent study, we carried out a comprehensive study on the identification of the ONE-N-acetyl-L-cysteine adducts and identified several advanced reaction products that originated from the initial Michael adducts (45).…”
Section: Discussionmentioning
confidence: 99%
“…A peculiar group of lipid-derived activated olefins is that generated by peroxidation of polyunsaturated lipids, which give rise to intermediate oxidation products among which trans-4-hydroxynonenal (HNE) is the most widely studied, due to its reactivity towards several biologically relevant proteins, such as albumin (Aldini et al, 2006(Aldini et al, , 2008, actin c (Toshimitsu et al, 2000;Aldini et al, 2005;Dalle-Donne et al, 2007a;Aldini et al, 2007a) cytochrome c (Isom et al, 2004), insulin (Fenaille, Guy, & Tabet, 2003) and myoglobin (Liu et al, 2003), while research on its more reactive cognate, trans-4-oxononenal (ONE), is more recent (Yocum et al, 2005;Zhu & Sayre, 2007).…”
Section: Mass Spectrometry and Protein Adductsmentioning
confidence: 98%
“…ONE reacts in vitro with human hemoglobin to yield an adduct with histidine residues in the aand b-chains. Mass spectrometric analyses showed that, while reactions performed on separated and denatured globins yielded modifications at His-20 of the a-chain and His-63 b-chain, reaction on the intact Hb tetramer only yielded modification of the latter with a cyclic 2 0 -pentyl-furane lipid-derived portion attached to the t-ring nitrogen of histidine through the 3 0 position (Yocum et al, 2005). Molecular modeling suggests that formation of this adduct seems to be linked to the presence of a specific arrangement of amino acid side chains in the neighborhood of the adducted histidine residue ( 62 AHGK 65 ) which favors cyclization of the lipid keto-aldehyde into a furan ring rather than reaction with the lysine e-amino group to yield a pyrrole derivative.…”
Section: Mass Spectrometry and Protein Adductsmentioning
confidence: 98%
“…A number of in vitro studies have shown that ONE and HNE react with various proteins that play key roles in regulating cellular functions such as cytochrome c, thioredoxin, hemoglobin, human serum albumin, and amyloid b [33][34][35]. In most cases, the specific modification sites were identified and the consequent biological effects were elucidated.…”
Section: Discussionmentioning
confidence: 98%